Cognitive aids: ’a must' for procedures performed by multidisciplinary sedation teams outside the operation room? - Eberl, Susanne (BMJ Case Rep, 2017)
The human brain might not perform optimally during stressful situations. Cognitive aids can help in such situations to carry out all necessary treatment steps in a correct order. We present the case of a severe anaphylactic reaction during a percutaneous radiological intervention to drain an echinococcosis cyst on the radiology suite outside the operation room (OR), in which cognitive aids were successfully used to optimise patient care by a multidisciplinary team. Cognitive aids do not replace experience and skills of the individual caregivers, but can be invaluable tools for multidisciplinary teams dealing with crisis situations outside the OR.